Strengthening Local Providers for Improved Rural Water Supply in Pakistan - World Bank (Washington, DC, 2016)
This synthesis report details the process, outputs, intermediate outcomes, lessons learned, and recommendations of the World Bank executed technical assistance (TA) on strengthening local providers for improved rural water supply in Pakistan implemented by the water and sanitation program of the global water practice. The development objective of this TA was to support the Government of Punjab (GoPunjab) in strengthening service provision by communities to ensure improved access to rural water supply, particularly for the marginalized and poor. These objectives were targeted through capacity building and introducing systems to better respond to community needs to manage rural water schemes via community based organizations (CBOs). This TA was primarily focused on the province of Punjab having a population of 100 million with of which 60 percent population live in rural areas. From inception, this TA was focused on institutional strengthening and sustainability. The back-up support mechanism for CBOs and information and communication technology (ICT) monitoring of scheme performance are extremely significant initiatives to have been integrated into the government system.